2013
DOI: 10.1007/s10384-013-0268-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the number of cytomegalovirus in anterior chamber and severity of anterior segment inflammation

Abstract: Measurements of the cytomegalovirus DNA amount is useful for evaluating the severity of the anterior segment inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 21 publications
(32 reference statements)
3
39
1
Order By: Relevance
“…CMV DNA copy numbers were measured at Tottori University by real-time PCR according to previously described methods 16 17. Briefly, DNA was extracted using a QIAamp DNA mini kit (Qiagen, Hilden, Germany) and amplified for the glycoprotein B gene of CMV using a LightCycler (Roche, Basel, Switzerland) 17. The copy number was calculated based on known dilutions of cloned glycoprotein B DNA.…”
Section: Methodsmentioning
confidence: 99%
“…CMV DNA copy numbers were measured at Tottori University by real-time PCR according to previously described methods 16 17. Briefly, DNA was extracted using a QIAamp DNA mini kit (Qiagen, Hilden, Germany) and amplified for the glycoprotein B gene of CMV using a LightCycler (Roche, Basel, Switzerland) 17. The copy number was calculated based on known dilutions of cloned glycoprotein B DNA.…”
Section: Methodsmentioning
confidence: 99%
“…5 A high CMV copy number was also identified as a substantial risk factor for IOP elevations. 6 In one recent study, Sobolewska et al reported that 36.4% of patients required surgical treatment in addition to oral valganciclovir administration to stabilize the IOP in CMV-related Posner-Schlossman syndrome. 7 Proper and early ganciclovir treatments can halt CMV activity; thus, the damage to the trabecular meshwork and corneal endothelium may be avoided.…”
Section: Introductionmentioning
confidence: 98%
“…However, proving a viral cause for all cases has been difficult due to its intermittent clinical course (Posner and Schlossman, 1953;Takusagawa et al, 2011;Van Gelder, 2008). The aqueous cytomegalovirus viral load has been positively correlated to the number of recurrent episodes and the number of glaucoma medications, where a high cytomegalovirus DNA copy number was a risk factor for increased IOP (Kandori et al, 2013). Moreover, treatment with antiviral therapy against cytomegalovirus decreased the attack frequency, the severity of inflammation, and the need for glaucoma medications during 14-43 months of follow-up .…”
Section: Ocular Infectionsmentioning
confidence: 97%